Albania : Staff Report for the 2002 Article IV Consultation, First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Requests for Modification and Waiver of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2003)
This paper examines Albania's 2002 Article IV Consultation, First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF), and Requests for Modification and Waiver of Performance Criterion. Economic growth appears to have fallen below a 7 percent estimated historical average, to 4.7 percent in 2002. High foreign investments and private remittances in 2001 have maintained robust import demand, reflected in a widening trade deficit in 2001 and the first half of 2002. The IMF staff supports the authorities' request for completing the first program review and the request for a waiver.